The NBN Futures Forum: Discussing the future ownership of Australia’s National Broadband Network - Campbell, Leith H; Milner, Murray (Journal of Telecommunications and the Digital Economy, 2019)
On 31 July 2019, TelSoc held an NBN Futures Forum in Melbourne to outline possible future ownership options for Australia’s National Broadband Network (NBN). Following an introduction to the objectives of the forum, four speakers outlined various options for future ownership of the NBN and identified pros and cons for these options. Then the floor was opened for questions from both the local and the wider virtual audience. The resulting conversation provided a useful insight into the range of social, economic, technical and policy issues that need to be considered in order to reach a balanced and properly informed view on the most appropriate future ownership model for the NBN.